2010
DOI: 10.14430/arctic384
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Season Survival of Female Lesser Scaup in the Northern Boreal Forest

Abstract: ABSTRACT. One hypothesis advanced to explain the decline in lesser scaup (Aythya affinis) populations during the past 20 years is that adult female survival has decreased. However, no survival probability estimates exist for the boreal forest, the region where most scaup breed. We captured and radio-marked female lesser scaup (n = 42) near Yellowknife, Northwest Territories, Canada, just before the breeding season in 1999 and 2000. Constant weekly survival probability was estimated using a Cormack-JollySeber m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Previous studies in the boreal-forest report that scaup female survival probability was 0.80 during the first 42 days of the breeding season, prior to brood rearing (Brook and Clark 2005), and 0.80 during the brood-rearing period (44 days; Walker and Lindberg 2005) for females that obviously bred. Therefore mortality during the nesting and broodrearing periods (0.36) constitutes a substantial portion of annual mortality of breeding scaup.…”
Section: Female Survivalmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies in the boreal-forest report that scaup female survival probability was 0.80 during the first 42 days of the breeding season, prior to brood rearing (Brook and Clark 2005), and 0.80 during the brood-rearing period (44 days; Walker and Lindberg 2005) for females that obviously bred. Therefore mortality during the nesting and broodrearing periods (0.36) constitutes a substantial portion of annual mortality of breeding scaup.…”
Section: Female Survivalmentioning
confidence: 93%
“…The relatively high survival may have been a result of low breeding effort at our study area. Brook and Clark (2005) did not determine reproductive status of females, but Safine (2005) found that survival probability of eggproducing white-winged scoters (Melanitta fusca) was lower than that of non-egg-producing females. Survival of female scaup may vary spatially across the continent (Lake et al 2006), and temporally, based on reproductive effort.…”
Section: Female Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Koons et al () demonstrated variability in the importance of different vital rates, with low reproductive success best‐explaining scaup population declines recorded after the mid‐1980s and juvenile female survival being more important than adult female survival in explaining long‐term population fluctuations. Most annual mortality of female scaup appears to occur during the breeding season when nesting females are vulnerable to predators (Rotella et al , Brook and Clark ) and productivity in the boreal forest was positively associated with abundance of small mammals, the staple prey of many duck nest predators (Brook et al ). This suggests that annual survival may be high when small mammals are abundant.…”
Section: Global Climate Indices Anticipated Ecological Effects In Wimentioning
confidence: 99%
“…Available breeding-season survival estimates for female ducks suggest considerable variation among species and populations and across breeding stages (e.g., Kirby and Cowardin 1986, Devries et al 2003, Brook and Clark 2005, Richkus et al 2005, Safine 2005). Notably, Kirby and Cowardin (1986) reported lower survival for female mallards (Anas platyrhychos) in Minnesota, USA, during the breeding season, with the lowest survival rates documented during the incubation period.…”
mentioning
confidence: 99%